Intracranial Atherosclerotic Burden and Cerebral Parenchymal Changes at 7T MRI in Patients With Transient Ischemic Attack or Ischemic Stroke - Lindenholz, Arjen; de Bresser, Jeroen; van der Kolk, Anja G.; van der Worp, H. Bart; Witkamp, Theodoor D.; Hendrikse, Jeroen; van der Schaaf, Irene C. (Frontiers in Neurology, 2021)
The relevance of intracranial vessel wall lesions detected with MRI is not fully established. In this study (trial identification number: NTR2119; www.trialregister.nl) 7T MRI was used to investigate if a higher vessel wall lesion burden is associated with more cerebral parenchymal changes in patients with ischemic stroke or TIA. MR images of 82 patients were assessed for the number of vessel wall lesions of the large intracranial arteries and for cerebral parenchymal changes, including the presence and number of cortical, small subcortical and deep grey matter infarcts, lacunes of presumed vascular origin, cortical microinfarcts, and periventricular and deep white matter hyperintensities (WMH). Regression analyses showed that a higher vessel wall lesion burden was associated with the presence of small subcortical infarcts, lacunes of presumed vascular origin, deep grey matter infarcts (relative risk 1.18; 95% CI 1.03-1.35), and presence of moderate to severe periventricular WMH (1.21; 95% CI 1.03-1.42) which are all manifestations of small vessel disease (SVD). The burden of enhancing vessel wall lesions was associated with the number of cortical microinfarcts only (1.48; 95% CI 1.04-2.11). These results suggest an interrelationship between large vessel wall lesion burden and cerebral parenchymal manifestations often linked to SVD or, alternatively, that vascular changes occur in both large and small intracranial arteries simultaneously.